Delayed Impact of 2-Oxoadipate Dehydrogenase Inhibition on the Rat Brain Metabolism Is Linked to Protein Glutarylation - Boyko, Alexandra I.; Karlina, Irina S.; Zavileyskiy, Lev G.; Aleshin, Vasily A.; Artiukhov, Artem V.; Kaehne, Thilo; Ksenofontov, Alexander L.; Ryabov, Sergey I.; Graf, Anastasia V.; Tramonti, Angela; Bunik, Victoria I. (Frontiers in Medicine, 2022)
Background. The DHTKD1-encoded 2-oxoadipate dehydrogenase (OADH) oxidizes 2-oxoadipate – a common intermediate of the lysine and tryptophan catabolism. The mostly low and cell-specific flux through these pathways, and similar activities of OADH and ubiquitously expressed 2-oxoglutarate dehydrogenase (OGDH), agree with often asymptomatic phenotypes of heterozygous mutations in the DHTKD1 gene. Nevertheless, OADH/DHTKD1 are linked to impaired insulin sensitivity, cardiovascular disease risks and Charcot-Marie-Tooth neuropathy. We hypothesize that systemic significance of OADH relies on its generation of glutaryl residues for protein glutarylation. Using pharmacological inhibition of OADH and the animal model of spinal cord injury (SCI), we explore this hypothesis. Methods. The weight-drop model of SCI, a single intranasal administration of an OADH-directed inhibitor trimethyl adipoyl phosphonate (TMAP), and quantification of the associated metabolic changes in the rat brain employ established methods. Results. The TMAP-induced metabolic changes in the brain of the control, laminectomized (LE) and SCI rats are long-term and (patho)physiology-dependent. Increased glutarylation of the brain proteins, proportional to OADH expression in the control and LE rats, represents a long-term consequence of the OADH inhibition. The proportionality suggests autoglutarylation of OADH, supported by our mass-spectrometric identification of glutarylated K155 and K818 in recombinant human OADH. In SCI rats, TMAP increases brain protein glutarylation more than OADH expression, inducing a strong perturbation in the brain glutathione metabolism. The redox metabolism is not perturbed by TMAP in LE animals, where the OADH inhibition increases expression of deglutarylase sirtuin 5. The results reveal the glutarylation-imposed control of the brain glutathione metabolism. Glutarylation of the ODP2 subunit of pyruvate dehydrogenase complex at K451 is detected in the rat brain, linking the OADH function to the brain glucose oxidation essential for the redox state. Short-term inhibition of OADH by TMAP administration manifests in increased tryptophan level and decreased levels of sirtuins 5 and 3 in the brain. Conclusion. Pharmacological inhibition of OADH affects acylation system of the brain, causing long-term, (patho)physiology-dependent changes in the expression of OADH and sirtuin 5, protein glutarylation and glutathione metabolism. The identified glutarylation of ODP2 subunit of pyruvate dehydrogenase complex provides a molecular mechanism of the OADH association with diabetes.